An assessment of road-verge grass as a feedstock for farm-fed anaerobic digestion plants. (July 2020) - Brown, Aaron E.; Ford, Judith S.; Bale, Catherine S.E.; Camargo-Valero, Miller A.; Cheffins, Nick J.; Mason, Patrick E.; Price-Allison, Andrew M.; Ross, Andrew B.; Taylor, Peter G.
Abstract: Cuttings from road-verge grass could provide biomass for energy generation, but currently this potential is not exploited. This research assessed the technical, practical and financial feasibility of using grass harvested from road verges as a feedstock in farm-fed anaerobic digestion (AD) plants. The methane potential (191 mL CH4 gDM −1 ) and digestion characteristics of verge grass were similar to those of current farm feedstocks; indicating suitability for AD. Ensiling had no significant impact on the biomethane generated. Testing co-digestions of verge grass with current farm feedstocks showed enhanced methane yields, suggesting that verge grass could be a valuable addition to AD feedstock mixes. In a case study of the UK county of Lincolnshire, potential volumes and locations of verge grass biomass were estimated, with capacities and locations of existing AD plants, to assess the potential to supply practical grass volumes. Grass harvesting costs were modelled and compared with other feedstock costs. Finally, the attitudes of AD operators to using verge grass were investigated to understand whether a market for verge grass exists. In a small survey all operators were willing to use it as a feedstock and most were prepared to pay over the estimated harvesting cost. If verge grass was legally recognised as a waste product it could be attractive to AD operators especially where financial incentives to use waste feedstocks are in place. In rural areas, verge grass could be harvested and co-digested by existing farm-fed AD plants, potentially reducing the cost of road verge maintenance and increasing biodiversity. Highlights: Verge grass had a methane potential of 222 mL CH4 gVS −1 or 191 mL CH4 gDM −1 . This is a similar methane potential to maize. Adding verge grass to existing AD feedstock mixes can enhance methane production. Estimated harvesting costs of under £18 t −1 were competitive with other feedstocks. Four out of five AD plant operators interviewed would pay for verge grass.